Improving genetic transformation rates in honeybees. Issue 1 (December 2018) - Otte, M.; Netschitailo, O.; Kaftanoglu, O.; Wang, Y.; Page Jr., R.; Beye, M.
Abstract Functional genetic studies in honeybees have been limited by transformation tools that lead to a high rate of transposon integration into the germline of the queens. A high transformation rate is required to reduce screening efforts because each treated queen needs to be maintained in a separate honeybee colony. Here, we report on further improvement of the transformation rate in honeybees by using a combination of different procedures. We employed a hyperactive transposase protein (hyPBaseapis ), we tripled the amount of injected transposase mRNAs and we injected embryos into the first third (anterior part) of the embryo. These three improvements together doubled the transformation rate from 19% to 44%. We propose that the hyperactive transposase (hyPBaseapis ) and the other steps used may also help to improve the transformation rates in other species in which screening and crossing procedures are laborious.